The Snags in Post Amnesty Militancy in the Niger Delta Region of Nigeria: The Curative Therapy (Global Journal of Management and Business Research, 2020)
The Niger Delta region of Nigeria, apparent said to be one of the richest and endowed deltas in the world and contributes about 80% of Nigeria's national wealth. The people of the area do not see and taste a diminutive of this wealth, rather faces a continues years of political and economic marginalization, environmental degradation, bad governance and policy inconsistency by the government, and the divide and rule policy of the oil companies which led to the emergence of militancy in the Niger Delta Region in early 2006. The various activities of militants have created a state of general insecurity in the region. This has led to the emergence of organized non-state armed groups, environmental activism and militancy in the Region. On assumption of office on May 29, 2009, the then President Musa Yar'adua announced Amnesty Programme for the Ex-militants as a means of bringing Peace to the Region. Moreover, this was strategic state policy for diffusing youth militancy in the Niger Delta and as a means of addressing the injustices in the Region.
Keywords: conflict; amnesty; peace; disarmament; demobilization; reintegration; rehabilitation; militancy